Development of Integrated Laboratory Management Information System - Arif Wibisono; Sudargo Sudargo; Ika Menarianti; Wijayanto Wijayanto (SISFORMA, 2022)
In 2021 PGRI Semarang University have at least 64 laboratories. This makes it a challenge for a private university to obtain funding independently in managing and maintaining assets of that size. It is necessary to develop an information system that could provide information input and information output facilities managed by the faculty and laboratory managers at the unit level of study programs and faculties, to be further reported as information to institutions and stakeholders. The researcher wants to make it a research goal, by designing and developing a Laboratory Information System (SILab) at the University of PGRI Semarang, which is validly tested according to the design results and is reliable or proven to be used well by users through user response tests.